Statement Pokok Periklanan Iklan Layanan Masyarakat Bahaya Stunting Di Kabupaten Pati Melalui Analisis Framing - Ali Muqoddas; Dwi Puji Prabowo; Abi Senoprabowo (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2024)
Stunting is a condition where a toddler's weight is smaller or his height is shorter than that of toddlers his age. Stunting cases in Pati Regency still exist with a prevalence of 20.6% in 18 village loci. Stunting cases that occur in Pati Regency are mostly caused by parents' wrong parenting patterns. If this problem is not addressed immediately, it can result in children experiencing mental, psychomotor and intellectual disabilities, and can affect the level of human resources in these fields. Therefore, the campaign needs to be carried out through public service advertisements. The research method in this design is qualitative with data collection using interviews and literature studies. The analytical method used is framing analysis which is used to find the main statement of the advertisement. The results of this research are in the form of a basic advertising statement in the form of an appeal to mothers with children in Pati district that they need to re-examine their hereditary beliefs. If there are parenting beliefs that conflict with health theory, then the mother must have the courage to stop that parenting pattern.